PERENCANAAN DAN PERANCANGAN INTERIOR KANTOR PT. GAMELOFT YOGYAKARTA - Febriwal . (Saraswati)
PT. GAMELOFT is a company that has a branch office in Klitikan region, Yogyakarta. To more increase the image and image it, from the factor service to clients also prioritizes comfort to employees is through from circulation, zone, space-forming elements, furniture, lighting, temperature, and color. Themes come from removal of information shaped logo with modern style, shape and material of the elements of space.Employee comfort get from the analysis of the function from the space that is based on the activities conducted, start from the settlement zone, circulation, lighting, and color as well as the facilities required by the user space.Election forms and use of materials and colors is one metod to achieve the image of the desired office interiors.The conclusion of this design is the employees can work more passion, interior design necessary to support all the activities and amenities that exist in the office. Application form, color, and material appropriate to the space will be able to provide value-added creation of atmosphere and character to any design style.Keyword : office design, modern , logo